(untitled) (Bangladesh Journal of Endosurgery, 2013)
Objective: To assess the efficacy and surgical morbidity associated with laparoscopic management of tubal ectopic pregnancy (EP) compared to that of open laparotomy. Study design: A randomized, prospective clinical trial was conducted at a private clinic setting, over a period between February 2007 and December 2012. Methods: A total of 166 women were admitted for suspected EP. Out of them 149 patients who had confirmed tubal EPs were subjected to different management options (conservative/medical/surgical). The diagnosis was based on the patients history, gynecological examination, ultrasound findings (transvaginal and or transabdominal), and serum [beta human chorionic gonadotrophin (?-hCG)] estimation. Based on inclusion criteria (only haemodynamically stable patients), a total of 85 patients were enrolled for the study. All the enrolled patients were managed surgically and randomly allocated to either laparoscopy group (n = 43) or laparotomy group (n = 42) by lottery method. Data regarding patients demographics, clinical presentation, diagnostic modalities, and treatment outcomes of two surgical techniques (laparoscopy or laparotomy) were recorded for every patient in a pre-designed data capture form. Statistical analysis was done by using SPSS version-15. Results: No significant differences were found between the two study groups regarding age, parity, gestational age, size & location of the ectopic gestation, the mean pre-operative ?-hCG level, history of previous surgeries, pelvic inflammatory disease, or endometriosis. Total operation time (entry to peritoneal cavity up to exit) needed in the laparoscopic group was less compared to that of laparotomy group (73.2 ± 26.8 min vs. 84.5 ± 34.3 min), which was not statistically significant (p > 0.001). The laparoscopic approach was associated with a reduction in intra-operative blood loss (subjective), need for post-operative analgesia (odds ratio 0.08, 95% CI, 0.040.43) and other post-operative morbidity (odds ratio 0.29, 95% CI, 0.180.55). The length of hospital stay following laparoscopic management was significantly less (p < 0.001) than that of laparotomy group (2.7 ± 0.6 vs. 3.2 ± 1.1 days). Conclusion: Laparoscopic management of EP offers major benefits in terms of less operating time, fewer analgesics, early recovery, and significantly shorter hospital stay within maximum safety and efficacy. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0015 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 35-38